The black circle - Carman, Patrick (New York : Scholastic, 2009)
Where are Amy and Dan Cahill? The two kids were last seen in Egypt, hunting for one of the 39 Clues that could make them the most powerful people on earth. But no one has seen the siblings since. Has the ruthless Irina Spasky finally tracked them down? Or worse ... the Madrigals?
Keywords: Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Russia -- Juvenile fiction; Mystery fiction; Adventure fiction